TEACHER’S TALKS IN CLASSROOM INTERACTION AT BANI ADUNG ISLAMIC BOARDING SCHOOL BANTEN - Ida Rahmawati; Sutrisno Sadji Evenddy; Ika Handayani (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2021)
The objectives of this research are to find out the categories and students’ perceptions of teacher’s talks that were applied by the English teacher in the teaching and learning process at Bani Adung Islamic Boarding School based on the framework Flander’s Interaction Analysis Categories (FIAC), and to know the students’ perceptions about the teacher’s talks. The participants of this research were the English teacher and the eighth grade students of the setting. The method of this research was qualitative descriptive method, and observation sheet, audio recording and questionnaire were used for data collection. The data taken from the teacher’s talks applied by the teacher in classroom activities were analyzed qualitatively. The result showed that the most dominant category was giving directions (29%), followed by asking the questions (27.5%), and the last category was accepting or using ideas of students (2.9%). The indirect talks were lower than direct talks. As a result, the teacher-centered method was found to be the most prevalent during classroom interaction. Students also preferred to be praised or encouraged, and effective language in the classroom was required. It is recommended that the teacher use all types of teacher talks in the classroom. They should, however, be based on the needs of the students.